2014
DOI: 10.1002/rem.21394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Active Cap Materials for Metal Retention in Sediments

Abstract: This study evaluated chemically active amendments used to construct active caps for remediating contaminated sediments. Three experiments assessed the effects of apatite, organoclay, zeolite, and biopolymers (chitosan and xanthan) on metal mobility, retention, and speciation. The first showed that the amendments individually and in mixtures (2 percent dry weight) reduced the concentrations of Cr, Co, Ni, and Pb in water extracts from reduced sediment. The second experiment, which used sequential extraction pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another material particularly effective to also remove metal(loids) is organoclay (OC), widely described in section 3, which consists of a bentonite layer modified with quaternary amines. Knox et al (2014) evaluated the effects of apatite, OC, zeolite, and biopolymers (i.e., chitosan and xanthan) on metal speciation, mobility, and retention. Their main results revealed that amendments reduced chromium (Cr), cobalt (Co), Pb, and Ni concentrations in water in reduced conditions.…”
Section: Isc Amendments For Inorganic Contaminationmentioning
confidence: 99%
“…Another material particularly effective to also remove metal(loids) is organoclay (OC), widely described in section 3, which consists of a bentonite layer modified with quaternary amines. Knox et al (2014) evaluated the effects of apatite, OC, zeolite, and biopolymers (i.e., chitosan and xanthan) on metal speciation, mobility, and retention. Their main results revealed that amendments reduced chromium (Cr), cobalt (Co), Pb, and Ni concentrations in water in reduced conditions.…”
Section: Isc Amendments For Inorganic Contaminationmentioning
confidence: 99%
“…Chemically reactive amendments have been used to improve contaminant retention in active capping systems (Knox et al 2014) and have potential to improve the retention properties of saltstone. Additionally, Li et al (2014) demonstrated the effectiveness of several active amendments (i.e.…”
Section: Fy2015 Objectivesmentioning
confidence: 99%
“…Capping materials used in laboratories and eld studies include activated carbon (Gu et al 2017), phoslock (Wang et al 2017), and natural/modi ed zeolites (Hong et al 2019;Jacobs and Waite 2004;Xiong et al 2018;Zhan et al 2019). Other materials newly studied include apatite (Knox et al 2014), attapulgite (ATT) (Yin et al 2016), biochar (Wang et al 2018;Zhu et al 2019), calcium peroxide (Zhou et al 2020), illite (Gu et al 2019), layered double hydroxide (Wu et al 2020), lanthanum-modi ed bentonite (Kong et al 2020), and zero-valent iron (Todaro et al in press).…”
Section: Introductionmentioning
confidence: 99%